Clues for the origin of the fundamental metallicity relations - I. The hierarchical building up of the structure - de Rossi, Maria Emilia (2007)
We analyse the evolutionary history of galaxies formed in a hierarchical scenario consistent with the concordance Lambda cold dark matter (CDM) model focusing on the study of the relation between their chemical and dynamical properties. Our simulations consistently describe the formation of the structure and its chemical enrichment within a cosmological context. Our results indicate that the luminosity–metallicity and the stellar mass–metallicity (LZR and MZR) relations are naturally generated in a hierarchical scenario. Both relations are found to evolve with redshift. In the case of the MZR, the estimated evolution is weaker than that deduced from observational works by approximately 0.10 dex. We also determine a characteristic stellar mass, Mc ≈ 3 × 1010 M⊙, which segregates the simulated galaxy population into two distinctive groups and which remains unchanged since z ∼ 3, with a very weak evolution of its metallicity content. The value and role played by Mc is consistent with the characteristic mass estimated from the SDSS galaxy survey by Kauffmann et al. Our findings suggest that systems with stellar masses smaller than Mc are responsible for the evolution of this relation at least from z ≈ 3. Larger systems are stellar dominated and have formed more than 50 per cent of their stars at z 2, showing very weak evolution since this epoch. We also found bimodal metallicity and age distributions from z ∼ 3, which reflects the existence of two different galaxy populations. Although SN feedback may affect the properties of galaxies and help to shape the MZR, it is unlikely that it will significantly modify Mc since, from z = 3 this stellar mass is found in systems with circular velocities larger than 100 km s −1